E-CRM Berbasis Web Pada Sistem Informasi Penjualan Toko Kue - Varissa Hikmatillah (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2022)
Bunda Bakery is a place that provides various kinds of cakes. Bunda Bakery has a variety of flavors and ingredients as well as various prices. So far, Bunda Bakery still sells manually, namely by word of mouth, so the range of sales is still limited and has not been able to expand to several areas. With the development of information technology, it is necessary to implement a very good strategy so as to make this Bakery business more accurate and improve sales and customer support services. Bunda Bakery shop which is located in Bunut Village across Jl. Ir. Sutami, Sidodadi, Kec. West Range City. Bunda Bakery shop which is engaged in the sale of various bakeries such as various breads, cakes and so on. Currently, the Bunda Bakery shop still sells manually by traveling from one area to another. Here the customer must also come to the manufacturer to see in more detail what the manufacturer sells. With web-based CRM, managing customer data becomes easier and helps in increasing loyalty and satisfaction so that customers do not easily turn to competitors and help companies in making decisions to improve quality and quantity for the company.